A Treatment Protocol for Management of Bacterial and Fungal Malignant External Otitis: A Large Cohort in Tehran, Iran. (July 2017) - Hasibi, Mehrdad; Ashtiani, Mohammadtaghi Khorsandi; Motassadi Zarandi, Masoud; Yazdani, Nasrin; Borghei, Pedram; Kuhi, Ali; Dabiri, Sasan; Hosseini, Reza; Sardashti, Sara
Aims: High rates of negative microbiologic test results highlight the potential role of empiric antimicrobial agents in management of malignant otitis externa (MOE). This study investigates the clinical presentation, laboratory findings, and response to empiric treatment in a large group of patients admitted to a tertiary academic hospital in Tehran, Iran. Methods and Materials: We recruited 224 patients diagnosed with MOE in a prospective observation from 2009 through 2015. All patients received a 2-agent antibacterial regimen at baseline (phase I). Patients with no improvement within 10 days and/or nonresponders to a second course of antibacterials were switched to antifungals (phase II). Response to treatment was observed and documented in both groups. Results: All patients had physical symptoms for more than 12 weeks before admission. In total, 127 patients responded well to antibacterials. Eighty-seven out of 97 patients who were switched to antifungals had complete response to treatment; patients in the latter group had significantly higher A1C levels at baseline. Conclusion: Our findings provide evidence to develop clinical guidelines that accelerate diagnosis and treatment of MOE to improve patient outcomes.